2020
DOI: 10.1016/j.aprim.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Burnout y malestar psicológico en los residentes de Medicina Familiar y Comunitaria

Abstract: Objetivo Estimar la prevalencia de burnout y malestar psicológico de los médicos residentes de Medicina Familiar y Comunitaria (MFyC) de dos unidades docentes y determinar su relación con el año de residencia, los estilos de vida y las condiciones laborales. Diseño Estudio transversal. Emplazamiento Atención Primaria. Participantes Se realizaron encuestas presenciales a los residentes de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
0
1
2
Order By: Relevance
“…The results demonstrated that 23.8% of responders exhibited psychological distress, which is higher than that reported in a previous study among dentists and dental hygienists in Israel (11.5%) (Shacham et al, 2020). The rate of psychological distress among dentists was 25.7%, which was lower than that in other medical specialties, such as neurologists in China (37.8%) (Zhou et al, 2017), trainee general practitioners in Spain (40.4%) (Ovejas-López et al, 2020), pediatric critical care physicians in the United States (30.5%) (Shenoi et al, 2018). Our study revealed that lower income, burnout, high job stress, career-choice regret, and lack of sufficient personal time were the risk factors for psychological distress in dentists.…”
Section: Discussioncontrasting
confidence: 55%
“…The results demonstrated that 23.8% of responders exhibited psychological distress, which is higher than that reported in a previous study among dentists and dental hygienists in Israel (11.5%) (Shacham et al, 2020). The rate of psychological distress among dentists was 25.7%, which was lower than that in other medical specialties, such as neurologists in China (37.8%) (Zhou et al, 2017), trainee general practitioners in Spain (40.4%) (Ovejas-López et al, 2020), pediatric critical care physicians in the United States (30.5%) (Shenoi et al, 2018). Our study revealed that lower income, burnout, high job stress, career-choice regret, and lack of sufficient personal time were the risk factors for psychological distress in dentists.…”
Section: Discussioncontrasting
confidence: 55%
“…Entre las respuestas encontradas al formulario, se objetiva una distribución bastante equitativa entre los distintos años de la residencia (R1-R4). Esto permite evitar grandes sesgos en cuanto a la subjetividad de algunas respuestas como por ejemplo el estrés percibido, puesto que este aumenta de forma exponencial con los años de residencia (18). Encontramos además respuestas de pediatras en formación tanto de hospitales de referencia como regionales y comarcales.…”
Section: Discussionunclassified
“…El estudio de este síndrome en centros de salud acreditados para formación sanitaria especializada puede ser aún de mayor utilidad por las repercusiones que podría tener sobre el personal en formación 18 . No ser tutor de residentes se ha descrito como factor de riesgo de burnout 9 .…”
Section: Despersonalización (Dp) 3 Baja Realización Personal (Rp)unclassified